-4
-x+3y+6x-6y=5x-3y
If you mean: 5x+2y+x-3y then it is 6x-1y
-7 + 5x > 6x + 1 subtract 1 from both sides -8 + 5x > 6x subtract 5x from both sides -8 > x
It is: x-5y simplified
-6x+3 = -7-5x 7+3 = 6x-5x 10=x
5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25
-5x+1 = 6x -5x-6x = -1 -11x = -1 x = 1/11
0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]
6x - 2x + 5x - 3First you want to have the x's by theirselves and the numbers by themselvesIt will still be:6x - 2x + 5x - 3Here, you do 6x - 2x.4x + 5x -3Then you combine 4x + 5x.9x - 3Simplified just like that
6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11
5x = 13123 - 6x 11x = 13123 x = 1193
5x(6x + 9y + 2)
Expression: x+10+5x Solve: x+5x=6x Answer: 6x+10
4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x
5x + x - 6x + 2x = 2x
6x-x+15-9= 6x-x=5x 15-9=6 5x+6=0 5x=-6 x=-1.2